Discovery and characterization of EIIB, a new α-conotoxin from Conus ermineus venom by nAChRs affinity capture monitored by MALDI-TOF/TOF mass spectrometry. (May 2017) - Echterbille, Julien; Gilles, Nicolas; Araóz, Romulo; Mourier, Gilles; Amar, Muriel; Servent, Denis; De Pauw, Edwin; Quinton, Loic
Abstract: Animal toxins are peptides that often bind with remarkable affinity and selectivity to membrane receptors such as nicotinic acetylcholine receptors (nAChRs). The latter are, for example, targeted by α-conotoxins, a family of peptide toxins produced by venomous cone snails. nAChRs are implicated in numerous physiological processes explaining why the design of new pharmacological tools and the discovery of potential innovative drugs targeting these receptor channels appear so important. This work describes a methodology developed to discover new ligands of nAChRs from complex mixtures of peptides. The methodology was set up by the incubation of Torpedo marmorata electrocyte membranes rich in nAChRs with BSA tryptic digests (>100 peptides) doped by small amounts of known nAChRs ligands (α-conotoxins). Peptides that bind to the receptors were purified and analyzed by MALDI-TOF/TOF mass spectrometry which revealed an enrichment of α-conotoxins in membrane-containing fractions. This result exhibits the binding of α-conotoxins to nAChRs. Negative controls were performed to demonstrate the specificity of the binding. The usefulness and the power of the methodology were also investigated for a discovery issue. The workflow was then applied to the screening of Conus ermineus crude venom, aiming at characterizing new nAChRs ligands from this venom, which has not been extensively investigated to date. The methodology validated our experiments by allowing us to bind two α-conotoxins (α-EI and α-EIIA) which have already been described as nAChRs ligands. Moreover, a new conotoxin, never described to date, was also captured, identified and sequenced from this venom. Classical pharmacology tests by radioligand binding using a synthetic homologue of the toxin confirm the activity of the new peptide, called α-EIIB . The Ki value of this peptide for Torpedo nicotinic receptors was measured at 2.2 ± 0.7 nM. Graphical abstract: